Preaching in the Digital Age: Exploring Digital Literacy Among Virtual Da’i in Ponorogo - Setyaningsih, Rila; Dwidarmawati, Rihan (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
The increasing transition of Islamic preaching (da’wah) to digital platforms has generated new requirements for digital literacy among community-level preachers (da’i). Although current research frequently emphasises content strategies and audience reactions, little attention has been directed towards the actual experiences of grassroots da’i in managing this shift. This study examines the development and use of digital literacy among virtual da’i in Ponorogo within their preaching practices. Employing a phenomenological methodology that included three participants, data were gathered via in-depth interviews, non-participant observation, and document analysis, and thereafter analysed using the European Commission’s digital literacy competence framework. The findings indicate that da’i often exhibit basic to intermediate levels of digital literacy, characterised by constrained technical abilities, instinctive rather than methodical material selection, and a reluctance to participate in interactive online communication. This study adds to the body of knowledge by providing an experienced viewpoint on community-based digital da’wah. It offers practical guidance for developing participatory training models incorporating technical, ethical, and communication skills.